Efficacy Of Intracanal Cryotherapy In Reducing Post-Endodontic Pain As Compared To Steroids - Bhagwat, Sumita; Mandke, Lalita Gauri; Vandekar, Mansi; Panjwani, Monica; Pawar, Aishwarya; Lakshmanan, Akash (Journal of Neonatal Surgery, 2025)
Introduction: Post-endodontic pain remains a frequent complication following root canal therapy, influenced by mechanical, microbial, and chemical factors. Traditional pharmacologic agents such as steroids have proven efficacy in pain mitigation; however, concerns regarding systemic side effects have encouraged exploration of alternative modalities. Cryotherapy, a non-pharmacologic technique utilizing cold saline irrigation, has shown promise in reducing inflammation and associated pain by inducing vasoconstriction and suppressing inflammatory mediators. Methods: This systematic review and meta-analysis followed PRISMA guidelines and was registered in the PROSPERO database (CRD42024564263). Electronic searches were conducted in PubMed, Scopus, Web of Science, and Cochrane Library for studies comparing intracanal cryotherapy and steroids in post-endodontic pain reduction. Eligible studies included randomized controlled trials assessing pain using standardized scales (VAS/NRS). Quality appraisal was performed using the Cochrane Risk of Bias tool and Newcastle-Ottawa Scale. Results: Twelve RCTs with 1,383 participants were included. Cryotherapy significantly reduced postoperative pain at 24–72 hours compared to steroids or control (mean VAS difference = –1.12; 95% CI: –1.45 to –0.79; I² = 45%). Subgroup analysis showed similar effectiveness for intracanal and intraoral cryotherapy. Minimal side effects were reported. The steroid groups also demonstrated pain reduction, but were associated with potential systemic risks and variability in application. Conclusion: Cryotherapy is a clinically effective and safe alternative to steroids for reducing post-endodontic pain. Its localized, non-invasive approach, minimal adverse effects, and simplicity of application make it an appealing adjunct in endodontic pain management. Further trials are needed to refine protocols and confirm long-term benefits.